Knowledge and attitude of dentist in districts of Tana Toraja and North Toraja regarding obstructive sleep apnoea: an overview: Gambaran pengetahuan dan sikap dokter gigi di Kabupaten Tana Toraja dan Toraja Utara mengenai obstructive sleep apnoea - Triantaglecia Rantebalik; Rasmidar Samad; Rini Pratiwi (Makassar Dental Journal PDGI Makassar, 2022)
Objective: This cross-sectional survey is aimed to describe the knowledge and attitudes of dentists in districts of Tana Toraja and North Toraja regarding obstructive sleep apnea (OSA). Methods: Using the Google Forms platform, a questionnaire adapted from the International Dental Journal 2021 entitled Knowledge and attitude of dentists towards obstructive sleep apnoe, an online questionnaire was distributed via Whatsapp to all dentists registered at the Toraja branch of PDGI (N=51). The sample included all dentists that participated in the survey. The questionnaire included 3 sections, namely demographics, knowledge, and attitude. Descriptive statistics were used to analyse the data. Results: Of the 51 dentists, 49 respondents take this questionnaire. As 57.1% scored below 12 in the total knowledge scores, and 57.1% scored below 3 in the total attitude scores based on Bloom’s Cut-off category. The mean total knowledge score was 10.31, while the mean total attitude score was 2.29. Conslusion: Dentists had low OSA-related knowledge and a negative attitude towards OSA. These findings suggest that dentists in Tana Toraja and North Toraja require more education and clinical training in OSA management to maximize patient benefits and minimise adverse outcomes.